Self-Care Predictor in Heart Failure: A Cross-Sectional Study Analysis of Person, Problem, and Environment Factors - Haryati, Haryati; Herawati, Tuti; Siswanto, Bambang Budi (Jurnal Berita Ilmu Keperawatan, 2026)
Understanding the predictors of self-care behavior in heart failure (HF) patients is crucial for designing effective interventions tailored to patient needs. The situation-specific theory of HF self-care emphasizes the interaction between the person, problem, and environmental as factors influencing self-care. This study aimed to identify predictors of self-care behavior in HF patients by examining individual characteristics, disease-related variables, and environment influences. This cross-sectional study was conducted on 110 HF patients at the outpatient cardiac clinic of Kendari City Hospital, selected using consecutive sampling method. Self-care behavior was measured using the European Heart Failure Self-Care Behavior Scale-9. The predictor variables included person-related factors (age, gender, occupation, self-efficacy as measured by the CSES, and spiritual well-being as measured with the FACIT-Sp12), problem-related factors (HF duration and symptom severity), and environmental factors (social support as measured by the 12-item MSPSS). A Binary logistic regression was used to identify the significant predictors. Variables with p-value < 0.05 in multivariate analysis were considered significant predictors of self-care. Among the participants (65.5% male; mean age 62.27 ± 9.10 years), 66.4% reported inadequate self-care. Higher Self-efficacy (AOR = 1.35; 95% CI: 1.15–1.58) and greater social support (AOR = 1.08; 95% CI: 1.01–1.16) were significantly associated with better self-care. In contrast, HF duration ≥ 2 years (AOR = 0.66; 95% CI: 0.46–0.96) was associated with poorer self-care. These findings recommend that nursing interventions should integrate person, problem, and environmental components, with an emphasis on strengthening self-efficacy and enhancing social support to optimize self-care among HF patients.